PROFIL PERSONALITY ATLET RENANG DI CLUB PSSC (PEMALANG SACK SWIMMING CLUB ) KABUPATEN PEMALANG (Universitas Negeri Semarang, 2021)
Gian Meliana Rizqi Listyani. 2021. Personality Profile of Swimming Athletes at PSSC Club (Pemalang Sack Swimming Club) Pemalang Regency. Thesis Department of Physical Education Health and Recreation Faculty of Sports Sciences, State Universitas Negeri Semarang. Lecturer Supriyono, S.Pd., M.Or. Keywords: Personality of PSSC Swimming Athletes The background of this research is the personality of swimming athletes at club PSSC, because personality influences the achievements of athletes. The role of personality is very important to know the personality traits of athletes that have. The formulation in this study is how the personality profile of swimming athletes in Club PSSC (Pemalang Sack Swimming Club) Pemalang Regency. The purpose in this study is to describe the personality profile of swimming athletes in Club PSSC (Pemalang Sack Swimming Club) Pemalang Regency. In accordance with Sport Personality Questionaire 20. The method used is a survey with a quantitative approach. The research location is at the Pssc Club pemalang district with a sample of 30 athletes. The samples in this study are saturated samples, data collection instruments are done with questionnaires and documentation. The data analysis used in this study was Ms.Excel and analyzed according to SPQ 20 norms. The results of this study consist of 4 aspects of indicators, namely achievement and competitiveness are at the average level, confidence and resilience are at the average level, interaction and sportsmanship are at the average level, power and aggressiveness are at a low level. The conclusion of this study is that the personality profile of swimming athletes at club PSSC from the 3 aspects shows average results and 1 aspect shows low results. Advice for athletes to increase power, and to be more confident, athletes should get used to a good personality in order to produce the expected performance.